Timber beam seismic design A numerical simulation - Abdoullah Namdar; Yun Dong; Yuyi Liu (Fracture and Structural Integrity)
In order to design a seismic timber beam, the effect of near-fault ground motion on timber beam has numerically been investigated, with reference to small displacement theory. The simulated near-fault ground motion is applied on the fixed base of a timber frame model. The beam is placed in single span of a timber frame. The beam has two different length sizes of 1.8 and 3.3 meters. The seismic load-displacement, seismic load-strain and strain-displacement have been calculated for all models and shown in graphs. The beam is designed with nonlinear analysis method and some mechanical properties for all models have been used, in numerical analysis. The numerical analysis results indicate that, the inertial interaction, energy dissipation and nonlinear deformation of beams in timber frames have directly related with frame span. In beams with a smaller length, higher seismic loading caused lower displacement. The displacement is reduced by reducing the length of the beam. The inertial interaction, energy dissipation and nonlinear deformation are changed respect to the length of the beam. The innovation of this paper is to develop cycling graphs by using ABAQUS, to improve design of timber frame and give an adequate explanation of seismic behavior of timber beam